Investigating neutrino masses in supersymmetric GUT extensions of the standard model - Choong, Zheng Yang (Nanyang Technological University, 2024)
The Standard Model of particle physics is the crowning achievement of modern science, providing a fundamental and complete description of the nature of matter, fields and their interactions. In 2012, the 5σ detection of the Higgs boson at CERN provided the last experimental verification for the Standard Model.